The conceptual metaphors of narrative structure: Gestural evidence for spatialized form in storytelling - Kimmel, Michael (Public Journal of Semiotics, 2014)
This paper explores conceptual tools whereby narratively competent adults conceptualize the structure of literary events, as opposed to their scene content. My focus lies on how narrativity as a mode of thought is constituted through metanarrative discourse and what role embodied representations play in it. This global level of story cognition takes the form of conceptual metaphors such as TIME IS A PATH, CAUSALITY IS FORCE, or THEMATIC REALMS ARE SPACES/PLANES. Two kinds of evidence for this claim are combined: (a) linguistic metaphors for story gist, and, more extensively, (b) metaphorical gestures that accompany story summarization and commentary. Based on footage in which German literary critics discuss books, my specific task is to identify the various dimensions of story logic that gestures refer to. Overall, the data suggests that narrative form is systematically rooted in spatial logic and that dedicated structural devices dynamically co-evolve with the retelling of content. The study thus contributes a demonstration of Lakoff’s (1987) “spatialization of form hypothesis”, i.e. the wide ranging claim that structural cognition is rooted in image schemas.